THE IMPACT OF CHRONIC RESTRAINT STRESS ON THE ESTROUS CYCLE IN NMRI MICE - Ristić, Jelena; Bogdan, Damir; Banović, Pavle (Medicinski podmladak, 2021)
Introduction: Stress is the term which involves phenomena present at several levels of biological organization induced by events called stressors. Stressors may be actual or perceived as threats to the homeostasis of the organism. Chronic stress is associated with women's reproductive health, especially with menstrual cycle disorders.Goal: To examine the impact of chronic restraint stress on the estrous cycle in NMRI mice.Material and methods: 12 mature female NMRI mice were randomly divided into control and experimental group. The induction of restraint stress was achieved in the experimental group for the next 14 days, 2 hours daily. Since the formation of groups vaginal lavages were taken from all mice. Lavages were used for making smears and analysed via light microscope in order to determine estrous cycle stages.Results: The estrous cycle was observed and divided into: proestrus, estrus, metestrus and diestrus.  During the adaptation, prolonged diestrus was dominantly present in both groups. During the induction of restraint stress in the experimantal group, the oscillation of oestrus stages was obseved as a deviation from diestus. Chi-square test showed statistically significant difference in  the deviation frequency, compared to control (p
Keywords: stress; estrous cycle; mouse; NMRI